Fungal pathogens affecting seedlings of Gmelina Arborea Roxb and Tectona Grandis L.F. and effect of three plant extracts - Anuagasi, C. L; Onuorah, J. A.; Okigbo, R. N. (International Journal of Agricultural Technology, 2017)
A total of ten fungi were isolated from different parts (root, stem and leaf) of G. arborea and T. grandis as well as the rhizosphere (soil). The fungal isolates were; Aspergillus flavus Link ex Grey, Aspergillus niger van Tieghem, Botryodiplodia theobromae Sacc., Fusarium oxysporum Schlecht, Geotrichium sp Link, Penicillium sp Link: Fries, Rhizoctonia solani D.C., Rhizopus stolonifer Ehrenberg ex corda, Sclerotium rolfsii Tode, Trichoderma viride Persoon ex Grey. The most frequently occurred fungi were Rhizopus stolonifer (23.73%), Botryodiplodia theobromae (22.03%), Aspergillus niger (15.25%) and Trichoderma viride (10.17%). Pathogenicity test revealed that A. niger, B. theobromae and R. stolonifer were pathogenic on on healthy seedlings of G. arborea and T. grandis. Standard antibiotics (Grisovid) was used as positive control comparative to plant extracts, while sterile distilled water was used as a negative control. All the plant extracts inhibited the growth of the test organisms at varying degrees. The effect of concentration of extracts on the test organism was significant (P<0.05). Colony diameter of the inhibition zone increased as the concentration of the extract increased (2.5%>5.0%>7.5%>10.0%). Ethanol and aqueous extracts of Allium sativum had the highest inhibitory effects on the mycelia growth of all test fungi, while the lowest inhibitory effects were recorded by ethanol and aqueous extracts of Carica papaya. Ethanol plant extract proved to be more potent than aqueous plant extracts. In all, 10.0% extract concentration gave the maximum inhibition on the three test fungi. The result of this research study showed that A. sativum, C. papaya and Z. officinale have effective inhibitory potentials against the fungi identified. Hence, their biological active ingredients can be exploited for the control of fungal pathogens affecting forestry nursery seedlings. The significance of these findings is discussed in relation to phytochemical as a means of disease control and the substitutions of plant extracts as potential antifungal agents and thus recommend their use to foresters as an alternative to synthetic fungicides.